DAMPAK RISIKO BISNIS, PERTUMBUHAN PENJUALAN, MEMPERBAIKI ASET PADA STRUKTUR PERMODALAN PERUSAHAAN PERDAGANGAN YANG TERDAFTAR DI INDONESIA SAHAM EXCAHNGE PERIODE 2016-2019 - Andre Fitriano (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The research objective is to explore and analyze the influence of business risk, sales growth and asset structure on the capital structure of a trading company. The approach used in this research is a quantitative approach. The type of research used is descriptive statistics. The nature of the study is causal relationships. The population of this study is 45 trading companies. The 23 companies as samples were drawn by using a purposive sampling technique in the four years of the study period. The results of this study show that simultaneously, business risk, sales growth and asset structure had an effect on capital structure. Partially, business risk had a significant effect on capital structure, sales growth had a significant effect on capital structure, asset structure did not have a significant effect on capital structure. The result of the determination coefficient test shows that 79.3% of the variation of the dependent variable is explained by the independent variable.